2018
DOI: 10.1089/jwh.2017.6656
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cervical Smears Performed by General Practitioners on the Cervical Cancer Screening Rate of their Female Patients: A Claim Database Analysis and Cross-Sectional Survey

Abstract: Cervical smears performed by GPs led to increased screening participation rates within the recommended age group of women. However, the size of this increase is insufficient to reach the expected participation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Our findings were in line with a study performed by Favre et al in 2018 in France, a nation where similarly GPs often do not perform pap smears 19. In their study, the participation rate in cervical cancer screening was slightly higher when a PHC physician performed smears and when the physician was female.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were in line with a study performed by Favre et al in 2018 in France, a nation where similarly GPs often do not perform pap smears 19. In their study, the participation rate in cervical cancer screening was slightly higher when a PHC physician performed smears and when the physician was female.…”
Section: Discussionsupporting
confidence: 92%
“…Although the authors of that study did not directly evaluate the willingness of PHC physicians to perform Pap smears, their findings are in line with our own observation that no associations exist between demographic and professional characteristics of PHC physicians’ and their willingness to perform cytology screening. Moreover, Favre et al’s findings support our assertion that promoting the provision of Pap smears by PHC physicians would lead to greater coverage [ 16 ].…”
Section: Discussionsupporting
confidence: 77%
“…In a study conducted in France by Favre et al, cervical smears performed by PHC physicians led to increased screening participation rates [ 16 ]. In their evaluation of the independent PHC physicians’ characteristics that predicted participation rates in patients, multivariate analysis showed that the only significant characteristic was whether the doctor performed smears or not.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous publications, we acknowledged as limits a follow up of only 2 years (as CCS used to be triennial in France) and no consideration of gynecology care facilities as confounding factors (8)(9)(10). These limits have been addressed in the current paper.…”
Section: Study Strengths and Limitationsmentioning
confidence: 98%